Stationary statistical experiments and the optimal estimator for a predictable component - Koroliouk, D. (Український математичний вісник, 2015)
A stationary autoregression process given by a difference stochastic equation is characterized by a two-dimensional covariance matrix under stationarity conditions. The optimal estimator function represented by a square variation of the martingale is used to obtain consistent estimators for the parameter of a predictable component.